Programming languages and systems : 25th European Symposium on Programming, ESOP 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, the Netherlands, April 2-8, 2016 : proceedings /: 25th European Symposium on Programming, ESOP 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, the Netherlands, April 2-8, 2016 : proceedings. (2016) - Unknown
No abstract available